(untitled) (CIPEEX, 2025)
The growing use of electronic cigarettes has caused significant changes in nicotine consumption, especially among adolescents and adults. This audience has migrated to the use of vaporization devices driven by the false perception that inhalation provides comfort and relief from signs of anxiety. However, despite their popularity, the long-term effects of electronic cigarette use are still poorly understood. On the other hand, these devices have been associated with health risks, especially in the development of respiratory and oral diseases, whose main causes are historically linked to smoking and can result in serious damage to the human body. The objective was to analyze the impact of the growth in the use of electronic cigarettes and its consequences for the health of the population, focusing on the respiratory system, diseases associated with prolonged use, and damage to physical and mental health. The aim is to conduct a critical review of the possible effects of this practice, which is still considered controversial, taking into account current legislation, epidemiological data, and the social perception of electronic cigarettes as an alternative to traditional smoking. This is a narrative review of the literature. The search was conducted in the SciELO, PubMed, and Google Scholar databases, using the descriptors “Electronic Cigarette,” “Respiratory System,” “Diagnosis,” and “Harm,” combined by the Boolean operators AND and OR. Articles published between 2021 and 2023, in Portuguese or English, with free access, that directly addressed the harm, risks, and injuries caused by electronic cigarettes in adolescents and adults were included. Studies that dealt with other negative consequences not closely associated with the topic were excluded. The selected studies highlight clinical manifestations of lung injuries related to e-cigarette use, including the EVALI outbreak. Short- and long-term health risks were identified, such as impacts on brain development and mental health. Evidence of reduced cell viability, DNA damage, and changes in inflammatory responses was also observed, contributing to significant physiological consequences. In addition, potentially carcinogenic substances were detected in the aerosols produced by these devices. It is concluded that despite the scarcity of long-term studies, the use of electronic cigarettes is already linked to several negative health effects. It is concluded that these devices are not safe alternatives to conventional tobacco, and further scientific studies are needed to deepen knowledge about their impacts. Public awareness and the development of effective public policies are also urgent in view of the growth in use among young people.